2019
DOI: 10.18568/internext.v14i2.465
|View full text |Cite
|
Sign up to set email alerts
|

Práticas Estratégicas de Internacionalização de Programas de Pós-Graduação: Estudo de Caso em uma Universidade Pública do Sul do Brasil

Abstract: A perspectiva da estratégia como prática social surgiu como uma das alternativas às pesquisas tradicionais na área de estratégia organizacional, passando a explicar a estratégia como algo que as pessoas fazem no seu dia a dia e não como uma propriedade das organizações. A internacionalização da pós-graduação brasileira se constitui em uma das principais metas do Sistema Nacional de Pós-Graduação. Nesse sentido, a perspectiva da estratégia como prática social pode ser utilizada para compreender as microdinâmica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…These results suggest prevailing domestic scientific collaborations in the PL studies, which agrees with findings reported by bibliometric studies on Brazilian scientific output (Leta & Chaimovich 2002, Sidone et al 2016. This low representation of internationally collaborative articles may be associated with the global view of the researcher (Neves et al 2019). Another possible explanation for this is the existence of geographical distance among countries and socioeconomic and linguistic barriers (Parreira et al 2017, Junlin et al 2020.…”
Section: Discussionsupporting
confidence: 88%
“…These results suggest prevailing domestic scientific collaborations in the PL studies, which agrees with findings reported by bibliometric studies on Brazilian scientific output (Leta & Chaimovich 2002, Sidone et al 2016. This low representation of internationally collaborative articles may be associated with the global view of the researcher (Neves et al 2019). Another possible explanation for this is the existence of geographical distance among countries and socioeconomic and linguistic barriers (Parreira et al 2017, Junlin et al 2020.…”
Section: Discussionsupporting
confidence: 88%
“…The low international collaboration in the production of articles reflects past difficulties in carrying out joint work. This pattern may be related to the fact that the realization of international collaboration, generally, results of the global view of the researcher (Neves et al, 2019). In addition, the existence of linguistic and cultural barriers and the geographical distance between countries makes it difficult to interact with foreign partners.…”
Section: Number Of Publications (Frequency %)mentioning
confidence: 99%